Impact of cigarette smoking on neurotrophic factors: insight to BDNF, GDNF, and NGF alterations - Behnoosh Miladpour; Farideh mohammadian; Parvaneh Alimardani; Mohammad Mahdi Mokhtari tabar; Azam Khedri (Egyptian Journal of Medical Human Genetics, 2025)
Abstract Background Cigarette smoking impacts neurotrophic factors, including brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor (GDNF), and nerve growth factor (NGF), through epigenetic modifications like DNA methylation. This study examines the effects of smoking on the methylation, gene expression, and serum levels of these factors. Methods Peripheral blood samples from 1,372 smokers and 1,231 nonsmokers were analyzed using methylation-specific PCR, qRT-PCR, and ELISA. Smokers were classified into light, moderate, and heavy groups based on nicotine dependence. Results Heavy smokers exhibited higher methylation of BDNF, GDNF, and NGF (p < 0.001). BDNF expression and serum levels were significantly reduced (p < 0.001), while NGF levels were elevated (p < 0.001). No significant differences were observed in GDNF serum levels. Conclusions Heavy smoking significantly alters neurotrophic factors through increased methylation, leading to reduced serum levels and gene expression of BDNF and elevated NGF levels, indicating damage to neuronal health and potential compensatory mechanisms. Conversely, GDNF levels remained unchanged despite methylation, suggesting complex regulatory pathways. These findings highlight the need for further studies to explore the interplay between smoking intensity, epigenetics modifications, and neurotrophic factor expression.